Business ethics as a novel issue in health care economics - Vrbová, H; Holmerová, I; Hrubantová, L (Sbornik lekarsky, 1997)
The problems of health care providing and solutions suggested to solve them should be discussed publicly at all appropriate levels in all developed countries. In this contribution, new approaches to understanding the problems of business ethics in health care are mentioned and recommended for discussion. An application of such principles of business ethics as trust, accountability, solidarity, transparency and social responsibility is considered in the four following areas. First, it is the allocation of limited resources in health care. This is the world-wide problem of the end of 20th century, as the development of medical technologies offers a wide range of new diagnostic and therapeutic procedures. In our country this coincides with the on-going, and still incompleted reform of health care. Second, the other area is that of connecting health-care and social problems, important namely for vulnerable groups such as children, the elderly and chronically ill. The third area is concerned with the privatization of health care, the newly emanating structure and function of the health care system and the role of health care provides in society. The last group contains issues concerning attempts to facilitate communication between health care specialists and general public, as well as attempts to support those institutions of the civic democratic society that are oriented toward health, sickness and health care providing.
Keywords: alokace zdrojů; Ethics, Medical; Trust; důvěra; sociální spravedlnost; Physician-Patient Relations; Health Care and Public Health; zranitelné populace; Česká republika; Ethics; sociální odpovědnost; Social Responsibility; Czech Republic; lékařská etika; kontinuita péče o pacienty; Persons; Social Justice; přidělování zdravotní péče; skupiny lidí; Humans; Health Care Rationing; Delivery of Health Care; Vulnerable Populations; poskytování zdravotní péče; Resource Allocation; etika; Continuity of Patient Care; lidé; vztahy mezi lékařem a pacientem